2012
DOI: 10.1371/journal.pone.0042221
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Changes during Presyncope and Recovery

Abstract: Orthostatic stress activates the coagulation system. The extent of coagulation activation with full orthostatic load leading to presyncope is unknown. We examined in 7 healthy males whether presyncope, using a combination of head up tilt (HUT) and lower body negative pressure (LBNP), leads to coagulation changes as well as in the return to baseline during recovery. Coagulation responses (whole blood thrombelastometry, whole blood platelet aggregation, endogenous thrombin potential, markers of endothelial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 31 publications
1
40
1
Order By: Relevance
“…Thus, the SYSTEMA cohort, being a real-life patient population, is more representative of the population-based cohorts included in previous epidemiological studies investigating relations between orthostatic hypotension and cardiovascular events. Moreover, in the aforementioned studies [10,11], orthostatic hypotension has not been systematically assessed. Consequently, the orthostatic stress model used in healthy volunteer-based studies cannot satisfactorily explain why patients with orthostatic hypotension differ in regard to cardiovascular risk from the normal population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the SYSTEMA cohort, being a real-life patient population, is more representative of the population-based cohorts included in previous epidemiological studies investigating relations between orthostatic hypotension and cardiovascular events. Moreover, in the aforementioned studies [10,11], orthostatic hypotension has not been systematically assessed. Consequently, the orthostatic stress model used in healthy volunteer-based studies cannot satisfactorily explain why patients with orthostatic hypotension differ in regard to cardiovascular risk from the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Orthostatic stress leads to increased intravascular pressure and enhances endothelial activation [10,11,19,20]. Under normal conditions, blood vessel walls are covered by a negatively charged layer of healthy endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suction applied during LBNP produces a pressure gradient that pulls fluid from the intravascular compartment to the extravascular space in the lower body, resulting in hemoconcentration (5,29,34). Plasma protein concentration and blood viscosity both increase, which creates a procoagulant milieu due to increased interactions between coagulation factors and cellular contributors to coagulation (12,17,21).…”
Section: Our Study Provides Noteworthy Data That Directly Compare Blomentioning
confidence: 99%
“…Cvirn and colleagues reported that the procoagulant effect of orthostatic stress persists for up to 20 min after presyncope, which is the endpoint of cardiovascular stress. Orthostatic stress has to be considered as an important risk factor for hypotension susceptibility, particularly in these patients in whom the activation of coagulation during orthostatic challenge persists after the challenge [19].…”
mentioning
confidence: 99%